2018
DOI: 10.1089/jmf.2017.4149
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Bioactive Compounds Isolated from Pressurized Steam-Treated Corni Fructus and Their Protective Effects Against UVB-Irradiated HS68 Cells

Abstract: This study evaluated the antioxidant and protective effects of bioactive compounds isolated from pressurized steam-treated Corni Fructus (PSC). We had previously tested the protective effects of the furan fraction containing 5-hydroxymethylfurfural (5-HMF), polyphenol fraction containing gallic acid, and iridoid glycoside fraction containing morroniside and loganin. We measured the potency of antioxidant activities of the bioactive compounds isolated from PSC via oxygen radical absorbance capacity (ORAC), 2,2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The iridoid-type compounds are believed to exert less relevant antioxidant activity than phenolic type compounds such as flavonoids and anthocyanins. It was proved that a fractions (1 mg/mL) of Corni fructus containing iridoids like loganin (content 83.07%) and morroniside (content 16.93%) or morroniside alone are less active than the fraction containing 5-hydroxymethylfurfural (content 21.10%), morroniside (content 5.40%) and loganin (content 64.05%) enriched in gallic acid (content 9.45%) [26]. Thus, it is suggested that minor compounds, other than iridoids, determine the antioxidant activity of CF extract.…”
Section: Discussionmentioning
confidence: 99%
“…The iridoid-type compounds are believed to exert less relevant antioxidant activity than phenolic type compounds such as flavonoids and anthocyanins. It was proved that a fractions (1 mg/mL) of Corni fructus containing iridoids like loganin (content 83.07%) and morroniside (content 16.93%) or morroniside alone are less active than the fraction containing 5-hydroxymethylfurfural (content 21.10%), morroniside (content 5.40%) and loganin (content 64.05%) enriched in gallic acid (content 9.45%) [26]. Thus, it is suggested that minor compounds, other than iridoids, determine the antioxidant activity of CF extract.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a simulated in vitro human digestion model was applied, and the stability of anthocyanins from the investigated fruits, as well as the changes in the antioxidant activity of the digested fruit extract were investigated. Although the anthocyanin profile, the total phenolic content, and the in vitro antioxidant capacity of the Cornelian cherry fruits were already elucidated by several research groups [10,11,17,18,19,20,21], this is the first study dealing with the impact of gastrointestinal digestion on their antioxidant activity and on the bioaccessibility of their anthocyanins.…”
Section: Introductionmentioning
confidence: 99%
“…The contents of oxypaeoniflorin ( 16) and 1,2,3,4,6-O-pentagalloyl glucose (30) were the highest in LYCM-3 extract. Interestingly, the content of paeonol (50) in the LYCM-1 extract was the highest. The contents of gallic acid (3), paeoniflorin (23), and 1,2,3,4,6-O-pentagalloyl glucose (30) were relatively stable in the four periods, with less than a one-fold difference.…”
Section: Determination Of Phytochemicals In CM Extractsmentioning
confidence: 95%
“…Gallic acid (3) was one kind of raw material for the synthesis of complex secondary metabolites in the early stage of growth, its content in CM was higher than others in a one-year growth period [41]. The content of paeonol (50) increases with the growth of CM. It is considered that paeonol (50) is one of the marker components in the growth and maturity of CM.…”
Section: Determination Of Phytochemicals In CM Extractsmentioning
confidence: 99%
See 1 more Smart Citation